2001
DOI: 10.1183/09031936.01.17509160
|View full text |Cite
|
Sign up to set email alerts
|

Observer variation in computed tomography of pleural lesions in subjects exposed to indoor asbestos

Abstract: To assess the reliability of computed tomography (CT) in detecting discrete pleural lesions, the interobserver and intra-observer variability in reading the conventional and high-resolution CT (HRCT) scans of 100 volunteers, who had worked for ¢10 yrs in a building with known asbestos contamination, was evaluated.In the first session, pleural abnormalities were detected by a single radiologist (A 1 ) in 13 subjects. In the second session, the scans were read again independently by the same radiologist (A 2 ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
2
8
0
1
Order By: Relevance
“…Results of ROC analysis of PCA localization to a sextant of the prostate in our study are closer to the general radiologists' performance in detecting extracapsular extension in the study by Mullerad and co-workers [18]. Interobserver and intra-observer agreement on MRI findings in our study are within the respective ranges published for such radiological examinations that are more difficult to interpret [37,40]. MRI of the prostate with a combined endorectal/body-phased-array-coil system at 1.5 T, including axial T1-weighted SE MR images and axial and coronal T2-weighted FSE MR images without fat signal suppression, as performed here, is a technically stable, routine examination of high standard [16,17].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Results of ROC analysis of PCA localization to a sextant of the prostate in our study are closer to the general radiologists' performance in detecting extracapsular extension in the study by Mullerad and co-workers [18]. Interobserver and intra-observer agreement on MRI findings in our study are within the respective ranges published for such radiological examinations that are more difficult to interpret [37,40]. MRI of the prostate with a combined endorectal/body-phased-array-coil system at 1.5 T, including axial T1-weighted SE MR images and axial and coronal T2-weighted FSE MR images without fat signal suppression, as performed here, is a technically stable, routine examination of high standard [16,17].…”
Section: Discussionsupporting
confidence: 81%
“…Several recent studies of radiological examinations whose interpretation is based on imaging signs rather than quantitative data demonstrate that intra-observer agreement tends to be better than inter-observer agreement [35][36][37][38][39][40]. Levels of agreement as measured by the kappa score appear to be higher when distinguishing signs in imaging are more easily defined.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, our results must be compared cautiously with those reported by (Marcus et al, 1987) due to the selection factors and the use of different tools for the radiological detection of asbestosrelated abnormalities. The prevalence of pleural plaques observed in this study was similar to that observed on HRCT examinations in subjects exposed to indoor asbestos pollution (De Raeve et al, 2001) or in urban transportation workers with low cumulative exposure to asbestos (Ameille et al, 2007).…”
Section: Discussionsupporting
confidence: 71%